The Collected Works of L.S. Vygotsky : the Fundamentals of Defectology (Abnormal Psychology and Learning Disabilities) - Rieber, R. W. (Robert W.) (Cognition and language., 1993)
This work is a translation of Volume 5 of Pedagogika's 6 volume series published in Moscow between 1982 and 1984. It includes Vygotsky's works on defectology originally published between 1924 and 1932, as well as posthumous, unpublished material.